1997
DOI: 10.1016/s0014-5793(96)01464-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved phosphorylation site modulating nuclear lamin polymerization

Abstract: Mitotic lamin disassembly results from phosphorylation at specific sites. In vitro, lamins can form head-to-tail polymers that disassemble upon phosphorylation by cdc2 kinase. A co-immunoprecipitation assay, employing Drosophila nuclear lamin Dm 0 fragments was used to study the effect of phosphorylation on head-to-tail binding. Phosphorylation of serine-50 by cAMP-dependent kinase inhibited head-to-tail binding in the same manner as phosphorylation of serine-42 by cdc2 kinase. Results suggest that multiple pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Recent work (Muranyi et al 2002;Park and Baines, 2006) demonstrated that herpesvirus infection led to recruitment of PKC to the nuclear membrane and subsequent phosphorylation of lamin B. Lamin B disassembly is associated with specific serine phosphorylation sites (Stuurman, 1997). This modification of the nuclear lamina occurred 10-12 hours post infection and served to promote budding of nucleocapsids at the inner nuclear membrane.…”
Section: ) Discussionmentioning
confidence: 99%
“…Recent work (Muranyi et al 2002;Park and Baines, 2006) demonstrated that herpesvirus infection led to recruitment of PKC to the nuclear membrane and subsequent phosphorylation of lamin B. Lamin B disassembly is associated with specific serine phosphorylation sites (Stuurman, 1997). This modification of the nuclear lamina occurred 10-12 hours post infection and served to promote budding of nucleocapsids at the inner nuclear membrane.…”
Section: ) Discussionmentioning
confidence: 99%
“…PKC-Several lamin kinases have been identified, including p34 cdc2 , PKC, and PKA (7,9,10,33). In an attempt to determine which kinase(s) mediates interphase sperm lamin B phosphorylation, sperm nuclei were incubated in egg cytosol containing increasing concentrations of the following kinase inhibitors: the nonspecific kinase inhibitors DMAP and staurosporine, the p34 cdc2 -specific inhibitors olomoucine and roscovitine (26), PKI, or the PKC-specific inhibitor chelerythrine (34).…”
Section: Lamin B Phosphorylation Is Inhibited By the Pkc-specific Inhmentioning
confidence: 99%
“…They include cyclin B/p34 cdc2 (7), S6 kinase II (8), protein kinase C (PKC) (4,9), and the cAMP-dependent protein kinase PKA (10). Down-regulation of PKA has also been shown to be essential for mitotic lamina disassembly (11).…”
mentioning
confidence: 99%
“…The nuclear lamina can be reconfigured by phosphorylation while operating as an important anchoring site for specific chromatin regions and contributing to the higher order chromatin organization in interphase (18). The relaxation of the nuclear lamina during the S-phase (19) and its dissolution during mitosis are caused by several different protein kinases, such as suPKC1 kinase in interphase sea urchin eggs (20), cyclin B⅐CDK-1 kinase (21-23), S6 kinase II (24), cAMP-dependent protein kinase (25), and PKC-␣ (26) or PKC-␤ II (27)(28)(29). Dissolution of the nuclear lamina is also needed to package collapsed and fragmented chromatin into apoptotic bodies (30).…”
mentioning
confidence: 99%